In Situ Synthesis of Copper Nanoparticles on Biocarbon Sheets for Surface-Enhanced Raman Scattering - Jianqiang Wei; Zelong Zhou; Junchao Qian; Yaping Wang; Jun Chen; Yunfei Sun (Nanomaterials, 2025)
A copper nanoparticles@porous biocarbon substrate was designed for Surface-Enhanced Raman Spectroscopy (SERS) via a simple reduction method. In the detection of three trace antibiotics, the substrate exhibits a very high Raman enhancement efficiency. This is partly because the biocarbon is rich in meso-micropores, which can rapidly trap target molecules. On the other hand, the copper nanoparticles embedded on the surface of the carbon sheets generate a large number of plasmonic hotspots, leading to an increase in Raman signal intensity. These results suggest that this substrate has utility for SERS applications in food safety, medicine, and water pollution detection.